Parametrizing turbulent exchange over summer sea ice and the marginal ice zone - Andreas, Edgar L.; Horst, Thomas W.; Grachev, Andrey A.; Persson, P. Ola G.; Fairall, Christopher W.; Guest, Peter S.; Jordan, Rachel E. (2010)
The article of record as published may be located at http://dx.doi.org/10.1002/qj.618 The surface of the Arctic Ocean in summer is a mix of sea ice and water in both leads and melt ponds. Here we use data collected at multiple sites during the year-long experiment to study the SurfaceHeatBudget of the Arctic Ocean (SHEBA)to develop a bulk turbulent flux algorithm for predicting the surface fluxes of momentum and sensible and latent heat over the Arctic Ocean during summer from readily measured or modelled quantities. The distinctive aerodynamic feature of summer sea ice is that the leads andmelt ponds create vertical ice faces that the wind can push against; momentum transfer to the surface is thus enhanced through form drag. In effect, summer sea ice behaves aerodynamically like themarginal ice zone, which is another surface that consists of sea ice and water. In our bulk flux algorithm, we therefore combine our SHEBA measurements of the neutral-stability drag coefficient at a reference height of 10 m, CDN10, with similar measurements from marginal ice zones that have been reported in the literature to create a unified parametrization for CDN10 for summer sea ice and for anymarginal ice zone. This parametrization predicts CDN10 from a second-order polynomial in ice concentration. Our bulk flux algorithm also includes expressions for the roughness lengths for temperature and humidity, introduces new profile stratification corrections for stable stratification, and effectively eliminates the singularities that often occur initerativeflux algorithms for very light winds. In summary, this new algorithm seems capable of estimating the friction velocity u∗ (a surrogate for the momentum flux) over summer sea ice with an absolute accuracy of 0.02–0.03 m s−1; the sensible heat flux, with an accuracy of about 6Wm−2; and the latent heat flux, with an accuracy of 3.5Wm−2. Both NSF (award 06-11942) and the National Aeronautics and Space Administration (award NNX07AL77G) supported ELA at NorthWest Research Associates ...